Landasan Psikologis dalam Pengembangan Kurikulum pada Mata Pelajaran PAI dan Budi Pekerti di Sekolah Menengah Atas: The Psychological Foundation in Curriculum Development for Islamic Religious Education and Character Education Subjects in Senior High Schools - Purnama, Jajang; Komarudin, Komarudin (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
This study aims to explore the psychological foundation in the development of Islamic Religious Education (PAI) curriculum at SMA Plus Al Ghifari Bandung. The background of this study underlines the importance of adjusting the curriculum to the needs and psychological abilities of students to achieve optimal educational goals. The method used is a literature study, with data collection through scientific journals, articles, books, and relevant school documents. The study was designed to analyze related literature without conducting field research. The main findings show that a psychology-based curriculum can increase the effectiveness of PAI learning and facilitate the understanding and application of religious values in daily life. The results of this study contribute to the educational literature, especially related to psychology-based curriculum development. The implications of this study emphasize the importance of integrating theory and practice in religious education as well as holistic and inclusive approaches in PAI curriculum development. Finally, this study proposes prospects for further development in the context of Islamic religious education. The limitations of the study include the focus on one school and the limitations of the literature study methodology.